Enhanced biostability and cellular uptake of zinc oxide nanocrystals shielded with a phospholipid bilayer. Issue 44 (1st November 2017) - Dumontel, B.; Canta, M.; Engelke, H.; Chiodoni, A.; Racca, L.; Ancona, A.; Limongi, T.; Canavese, G.; Cauda, V.
Abstract : The surface chemistry and charge of zinc oxide nanocrystals influence their behaviour in biological fluids. A novel lipid bilayer assembly is developed to shield ZnO nanocrystals improving their stability and cell internalization. Abstract : The widespread use of ZnO nanomaterials for biomedical applications, including therapeutic drug delivery or stimuli-responsive activation, as well as imaging, imposes a careful control over the colloidal stability and long-term behaviour of ZnO in biological media. Moreover, the effect of ZnO nanostructures on living cells, in particular cancer cells, is still under debate. This paper discusses the role of surface chemistry and charge of zinc oxide nanocrystals, of around 15 nm in size, which influence their behaviour in biological fluids and effect on cancer cells. In particular, we address this problem by modifying the surface of pristine ZnO nanocrystals (NCs), rich of hydroxyl groups, with positively charged amino-propyl chains or, more innovatively, by self-assembling a double-lipidic membrane, shielding the ZnO NCs. Our findings show that the prolonged immersion in simulated human plasma and in the cell culture medium leads to highly colloidally dispersed ZnO NCs only when coated by the lipidic bilayer. In contrast, the pristine and amine-functionalized NCs form huge aggregates after already one hour of immersion. Partial dissolution of these two samples into potentially cytotoxic Zn 2+ cations takes place, together with the precipitation of phosphate and carbonate salts on the NCs' surface. When exposed to living HeLa cancer cells, higher amounts of lipid-shielded ZnO NCs are internalized with respect to the other samples, thus showing a reduced cytotoxicity, based on the same amount of internalized NCs. These results pave the way for the development of novel theranostic platforms based on ZnO NCs. The new formulation of ZnO shielded with a lipid-bilayer will prevent strong aggregation and premature degradation into toxic by-products, and promote a highly efficient cell uptake for further therapeutic or diagnostic functions.